Revision of the Neotropical caddisfly genus Phylloicus (Trichoptera: Calamoceratidae) - Prather, Aysha L. (Zootaxa, 2003)
Systematics of the genus Phylloicus are reviewed. Illustrations, a generic diagnosis, and descriptions are provided for males and females. 61 nominal species are recognized, of which 26 are newly described: P. adamsae (Peru), amazonas (Brazil, Peru, Venezuela), auratus (Peru), bertioga (Brazil), bicarinatus (Peru), bidigitatus (Brazil), blahniki (Costa Rica), cordatus (Venezuela), cressae (Venezuela), elektoros (Brazil, Venezuela), ephippium (Ecuador), flinti (Peru), holzenthali (Venezuela), llaviuco (Ecuador), munozi (Costa Rica), panamensis (Panama), paprockii (Brazil), passulatus (Venezuela), paucartambo (Peru), perija (Venezuela), pirapo (Paraguay), quadridigitatus (Brazil), quitacalzon (Peru), spinulacolis (Venezuela), trichothylax (Ecuador), and yolandae (Brazil). Phylloicus ornatus (Banks) and P. centralus (Navás) are designated as junior synonyms of P. aeneus; P. priapulus Denning and Hogue is designated a junior synonym of P. lituratus; and P. latus (Navás) and P. sagittosa (Ross) are designated as junior synonyms of P. nigripennis. Phylloicus crenatus Navás, P. medius Müller and P. tricalcaratus (Ulmer) are considered nomina dubia. Lectotypes are designated for P. bromeliarum, P. major, and P. spectabilis. A neotype is designated for P. abdominalis.